What is an ID? - Olysha Magruder; Daniel Arnold; Mel Edwards; Shaun Moore (Online Learning, 2019)
Instructional design positions in higher education require greater depth and breadth of knowledge, far beyond the bulleted qualifications found in typical job descriptions. The eDesign Collaborative Research Team wished to explore the discrepancies that exist between commonly identified competencies and those deemed necessary by instructional designers (IDs) actively working in postsecondary education. This study identifies the work performed by instructional designers and compares that work to the competencies and tasks identified in literature focused on instructional design and designers. Likewise, the study sought to explore the career plans and goals of IDs and their access to professional development.